Magmatic source, petrogenesis, and tectonic setting of the Concepción del Oro Igneous Complex: a geochemical and isotopic (Rb–Sr and Sm–Nd) study of a late complex of the Cretaceous–Eocene Mexican Magmatic Arc - Reneé González-Guzmán; Fernando Velasco-Tapia; Bodo Weber; Peter Schaaf; Rogelio Sosa-Valdés; Luigi Solari (International Journal of Earth Sciences, 2023)
During the Mexican fold-and-thrust belt tectonics, the inboard migration of long-term cordilleran magmatism typifies the geological setting during the Cretaceous–Paleogene period. The Concepción del Oro Igneous Complex (COIC) represents one of the most internal and isolated magmatic pulses that occurred during this magmatic activity. In this work, plutonic rocks from the COIC were studied using petrography, U–Pb geochronology, whole rock and zircon geochemistry, and Rb–Sr and Sm–Nd isotopes. Petrographic observations reveal mainly fine-to-coarse-grained granodioritic composition for most plutonic masses. U–Pb zircon analyzes of four samples from the largest plutonic center of the COIC yielded ages ranging from 42.6 ± 0.2 Ma to 41.8 ± 0.1 Ma. The granodiorites exhibit geochemical features typical of I-type, high-K calc-alkaline, Magnesian rocks. The chondrite-normalized REE diagram summarizes enrichment of LREE ([La/Yb] N = 5.94–19.19) and moderate to slightly negative Eu anomalies (Eu/Eu* = 0.63–0.94). In addition, the mantle-normalized spider diagram shows enrichment of LILE, such as Rb and Ba, and depletion of HFSE, such as Nb, Ta, Ti, and P. Whole-rock and zircon geochemistry indicate a post-collisional setting with an inherited magmatic arc fingerprint. Ti-in-zircon temperatures and zircon saturation thermometry suggest a magmatic origin from evolved and relatively cold melts (~ 700 °C). Moreover, the systematic variations in the ratios of highly incompatible elements, such as La/Sm (6.54–3.79) and Rb/Sr (0.32–0.10), and relatively narrow ranges in Zr/Hf (36.25–48.84) and 147 Sm/ 144 Nd (0.0941–0.1261), suggest fractional crystallization as the main petrogenetic process involved in the formation of the COIC rocks. Whole-rock isotopic data suggest a magma source mixing juvenile material with older continental crust, as indicated by 87 Sr/ 86 Sr ( t = 40) ratios between 0.704583 and 0.707783, 143 Nd/ 144 Nd ( t = 40) ratios varying in the ranges of 0.512478–0.512702 (εNd ( t = 40) = from + 2.18 to − 2.10), and TDM (Nd) ranging from 1.03 to 0.62 Ga. We conclude that the parental source of the COIC was derived from partial melting of the lower crust triggered by emplacement of an underplated magma at the base of the crust during the end of an orogenic cycle.